2003
DOI: 10.1074/jbc.m301253200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Regulates Focal Adhesion Assembly in Human Brain Microvascular Endothelial Cells through Activation of the Focal Adhesion Kinase and Related Adhesion Focal Tyrosine Kinase

Abstract: Vascular endothelial growth factor (VEGF) plays a significant role in blood-brain barrier breakdown and angiogenesis after brain injury. VEGF-induced endothelial cell migration is a key step in the angiogenic response and is mediated by an accelerated rate of focal adhesion complex assembly and disassembly. In this study, we identified the signaling mechanisms by which VEGF regulates human brain microvascular endothelial cell (HBMEC) integrity and assembly of focal adhesions, complexes comprised of scaffolding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 62 publications
7
97
1
1
Order By: Relevance
“…Tat induced the formation of focal adhesions in HBMECs when seeded on fibronectin, and pretreatment with Tat-specific Abs or with the specific inhibitor SU-1498, which inhibits VEGFR-2 receptor phosphorylation, blocked the ability of Tat to stimulate focal adhesion assembly. These effects of Tat on focal adhesion assembly were very similar to those observed with VEGF (28). This suggests that Tat mimics VEGF-mediated effects in brain endothelium via its binding to VEGFR-2, leading to VEGFR-2 activation and VEGFR-2 mediated signaling in BMEC.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Tat induced the formation of focal adhesions in HBMECs when seeded on fibronectin, and pretreatment with Tat-specific Abs or with the specific inhibitor SU-1498, which inhibits VEGFR-2 receptor phosphorylation, blocked the ability of Tat to stimulate focal adhesion assembly. These effects of Tat on focal adhesion assembly were very similar to those observed with VEGF (28). This suggests that Tat mimics VEGF-mediated effects in brain endothelium via its binding to VEGFR-2, leading to VEGFR-2 activation and VEGFR-2 mediated signaling in BMEC.…”
Section: Discussionsupporting
confidence: 64%
“…Our previous studies have shown that VEGF regulates focal adhesion assembly in HBMECs through activation of FAK and related adhesion focal tyrosine kinase (28). Because Tat is known to induce the expression of some cytokines and growth factors in ECs, we examined whether the effects of Tat on focal adhesion assembly in HBMECs are mediated via VEGF induction.…”
Section: Tat Effects On Focal Adhesion Assembly Were Not Mediated Thrmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that, during cell adhesion, clustering of integrins leads to the recruitment of FAK and PYK2 to the newly formed focal adhesion sites and activates the phosphorylation of a variety of downstream pathways (71). As for PYK2 activation mechanisms, it has been shown that this tyrosine kinase displays an integrin-dependent phosphorylation in lymphocyte B, CMK cells, and osteoclasts (52,53,62).…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinase (FAK) is a potential target for this approach because it mediates both integrin and growth factor signaling in the activation of SMC proliferation and migration, as well as the expression of the matrix metalloproteinases that mediate migration and vascular remodeling [141][142][143][144][145][146][147]. Upon integrin activation via ECM or growth factor stimulation, FAK localizes intracellularly to focal adhesion complexes with its carboxyterminal FAT domain, autophosphorylates itself, and iniiates various cell survival, migration, and proliferation signaling cascades [148].…”
Section: Inhibiting Smc Proliferation and Migrationmentioning
confidence: 99%